Uses of ICT in English teaching in primary schools in Wei Nan city, China - Ab. Samad, R.S.; Houque, K.E.; Othman, A.J.; Rahmad Sukor, M.I.; Megat Daud, M.A.K.; Ma, Y. (Macrothink Institute, 2013)
The purpose of this study is to identify the management of ICT (Information Communication Technology) in English teaching in primary schools in Wei Nan city, China. This study used a survey questionnaire on the role of ICT in primary English teaching and learning. The data obtained from the study for answering the research questions also exploring the outcomes of the use of ICT in primary English programmesr and the current challenges in exercising the use of ICT in Education. The results showed that the use of computers makes classes more vivid, motivation and effective to students.